Rupture uterus in a tertiary care centre - Dhar, Gautami; Sarma, Hem Kanta Dev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Rupture uterus is an obstetric life-threatening complication with poor maternal and fetal outcome. The most common risk factor is previous uterine surgeries. Incidence is 0.3/1000 to 7/1000 deliveries in developing countries like India. According to WHO, incidence is 5.35 per 10000 live births. It accounts for 5-10% of maternal deaths. Uterine rupture is associated with significant uterine bleeding, fetal distress and demise, expulsion or protrusion of fetus, placenta or both into the abdominal cavity and need for laparotomy and prompt delivery of the baby, uterine rent repair, or hysterectomy. The objective of this study was to find out the incidence of uterine rupture in Fakhruddin Ali Ahmed Medical College and Hospital, Barpeta and to evaluate its causes. Methods: This hospital based descriptive study of rupture uterus was conducted over a period of 1 year from January 2021 to December 2021, in the department of obstetrics and gynaecology, Fakhruddin Ali Ahmed Medical College, Barpeta, Assam. All cases of rupture uterus, who were referred from periphery and admitted in our hospital or who developed this complication during hospital stay, were included in the study. Results: Uterine rupture is one of the most catastrophic complications in obstetrics. The incidence of uterine rupture in our centre was 0.43%. Previous caesarean section accounted for 38.46% of uterine rupture, that too in the lower segment (94.73%). Subtotal/total hysterectomy was done in 30.76% cases and 69.23% cases were repaired. Perinatal mortality was 92.30%, 7.69% of cases were live birth, as these cases were rightly diagnosed, and prompt and timely management was done. Conclusions: Rupture uterus most commonly occurred in scarred uterus. Identification of high-risk pregnancy, judicious caesarean section, proper labour monitoring with the use of partograph, early diagnosis and prompt management are essential in reducing its occurrences.